Aprendizagem na educação superior: a auto-trans-formação do estudante na Aprendizagem Baseada em Problemas (Problem-Based Learning - PBL) - Almeida, Elisa Carneiro Santos de (2015)
This study establishes as the focus of investigation on the learning processes of students of Higher Education. Specifically, we will seek to understand the learning characteristics in the perspective of the Problem-Based Learning (PBL) methodology by point of view of Medical College students at State University of Feira de Santana - UEFS. Consequently, the studies developed about: learning adult student; active methodologies and the Problem-Based Learning (PBL) methodology, that acquire fundamental importance to the development of this research. In this sense, we will explain the adult learning and its specificities from the perspective of authors such as: Oliveira (2005), Nogueira (2009), Vigotski (1996; 2007), Placco and Souza (2006) among others. In discussions about active methodologies we bring to the scene studies such as Anastasiou (2007; 2009), Berbel (1998), Ribeiro (2010) and Oliveira (2010). Thus, to discuss the PBL methodology, articulate the theoretical analysis of the following authors: Barrows (1996), Chaer (2010), Feuerwerker (2002), Komatsu (2010), Mamede (2001) and Ribeiro (2010). Under these perspectives, we developed a qualitative methodological approach of field research, exploratory and descriptive. By understanding that the reports of the students are strengthened in situations in which there are opportunities for knowledge exchange. Thus, we elected as main data collection instrument conducting focus groups with students of 3rd and 4th year from Medicine College at UEFS. Indeed, the analysis was realized from the assumptions drawn by Bardin (2001), on the content analysis which enabled the creation of three categories, namely: learn to be subject of learning; learn from each other; learn by praxis. So the results reveal the specifics of learning through PBL methodology. The reports also reveal that, although facing some problems in the Medical College at UEFS, the objectives of the proposed methodology of the PBL are satisfactorily achieved. Therefore, we seek with this study contribute to the (re) think the learning process bases on Higher Education, in favor of an university that develops the student's autonomy for its effective personal and professional development.